PERUBAHAN PERAN PEREMPUAN DALAM PEREKONOMIAN RUMAH TANGGA SUKU DAYAK DI DESA KUALA ROSAN, MELIAU, KALIMANTAN BARAT - Lathifah, Af’idatul (Sabda: Jurnal Kajian Kebudayaan, 2016)
The change of economic resources in society also often followed by changes of social relations between community members. In remote area of Indonesia, the role of women in the family economy commonly is only a complementary role. However, in the village of Kuala Rosan, the family's economic responsibility is also taken by women, due to the growth of rubber and palm agriculture in the village of Kuala Rosan which needs more labor. This article is the result of a study conducted in the village of Kuala Rosan, Kecamatan Meliau, Kabupaten Sanggau, West Kalimantan, using qualitative research method with descriptive analysis. The results showed that women have a significant economic role. The views on women also change, as changes in their role within the household, women have more access to economic resources. However, men remain important decision makers in the household.Â